Pengaruh struktur kepemilikan, struktur modal dan ukuran perusahaan terhadap risk management disclosure pada perusahaan perbankan yang terdaftar di Bursa Efek Indonesia - Kristiono '; Zulbahridar '; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study aimed to examine the effect of management ownership on risk management disclosure, the effect of institution ownership on risk management disclosure, the effect of capital structure on risk management disclosure and the effect of firm size on risk management disclosure. The sample was taken using the method of purposive sampling from banking firm listed Indonesian Stock Exchange(BEI) in 2010-2012. The sampling used was of 108 samples from 36 banks period of 3 years. The method of analysis in this study using multiple regression. The results of this study indicate that firm size effect on risk management disclosure. While management ownership, institution ownership, and capital structure does not effect on risk management disclosure.Keyword: Management ownership, institution ownership, capital structure, firm size, risk management disclosure.